Asia's organic sprouts - Branigin, William (2010)
A tendency toward protectionism and a bias for Western markets is limiting the development of organic agriculture in the region.
Organic growth -- Touting organic's benefits -- Confronting the obstacles -- Grappling with certification.
Keywords: Organic farming -- Social aspects; Organic farming -- Economic aspects; Organic farming -- Environmental aspects; Sustainable agriculture -- Social aspects; Sustainable agriculture -- Economic aspects; Sustainable agriculture -- Environmental aspects; Sustainability; Quality of life; Rural development; Sustainable development